Diversity of edible mollusc (Gastropoda and Bivalve) at selected division of Sarawak, Malaysia. - Hamli, Hadi; Idris, Mohd Hanafi; Abu Hena, Mustafa Kamal; Wong, Sing King (Indonesian Society for Knowledge and Human Development, 2012)
Diversity of edible mollusc was studied at eight divisions of Sarawak from August 2010 to May 2011. At each division, diversity and number of species were collected from road site selling out lets and local wet markets. Total number of mollusc was comprised of 29 species namely Solen regularies, S. lamarckii, Pharella acutidens, Anadara granosa, Pholas orientalis, Gluconome virens, Circe scripta, Anodonta woodina, Paphia undulata, Amusium pleuronectes, Meretrix meretrix, M. lyrata, Polymesoda bengalensis, P. erosa and P. expansa for bivalve and Cerithidea rizophorarum, C. obtusa, Telescopium telescopium, Clithon retropictus, Nerita articulate, N. chamaeleon, N. albicilla, Ellobium aurisjuda, Trochus radiates, Planaxis sulcatus, Monodonta labio, Turbo crasus, Thais aculate and Melo melo for gastropod. The species number of bivalve was recorded highest (15 species) in mollusc group from Sarawak. Mollusc diversity was found highest (14 species) in Bintulu and lowest (1 species) in the division of Sarikei. From this study, there is a wide chance of research to further explore both on the possibility of commercial value and ecosystem conservation.